Impact of the loan guarantees program reactiva on the performance of Peruvian companies - Marcos Ceron; Gerald Cisneros; Rafael Nivin (Graduate Institute of International and Development Studies, 2023)
Amid the global COVID-19 crisis, governments worldwide introduced measures to support private enterprises. This study utilizes a newly curated panel database, encompassing the financial records of firms in Peru, to investigate the impact of a substantial governmentbacked loan guarantee program, known as "Reactiva Peru", on the performance of mediumsized Peruvian firms. To address the non-random allocation of loans, our empirical approach combines matching techniques and difference-in-differences methods, drawing upon previous research (Girma et al., 2007; Heyman, 2007). Our findings reveal that the Reactiva program led to heightened liquidity levels among beneficiary firms, albeit with an associated increase in indebtedness. Regarding profitability, the observed impacts on treated companies were not notably positive, except for a modest uptick in the net profit margin. This study contributes valuable insights into the efficacy of public credit support programs during crises, highlighting both their advantages and potential trade-offs for medium-sized enterprises.
Keywords: G18; G21; G28; H81; 330; Loan Guarantees; COVID-19 pandemic; credit risk; bank lending